(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
The main problem discussed in this article is how the efforts carried out by the Garuda II contingent in the Republic of the Congo. Research methods used used is a historical method which includes several steps, namely heuristics (collecting sources) both oral and written sources, source criticism, interpretation, and historiography. To deepen the analysis, the authors use the approach of the science of sociology, the science of international relations. The research technique used is the study of literature. Based on the results of the research, the Government of Indonesia participated in sending peacekeeping forces to the Republic of Congo under the auspices of the United Nations in 1960. Activities undertaken by the Garuda II Contingent Force namely to overcome and mediate rebellions that occurred in the Republic of Congo and conduct patrols to areas that often occur conflicts such as overcoming the battle of sending Garuda II contingent to the City of Boende and Coquihalville, the battle of Kamina, a mine explosion event in Kamina. From these activities the Garuda II Contingent Forces succeeded in carrying out their duties so as to have a very positive impact on the Indonesian contingent troops so that the following year the Indonesian Government sent the Garuda Contingent back in 1962.